Inovasi Layanan Jemput Bola di Taman Baca Masyarakat Teras Baca Sekar Kinasih Sidareja - Ferina Endang Rahayuningsih; Sukaesih Sukaesih; Asep Saeful Rohman; Evi Nursanti Rukmana (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2020)
The research carried out has the aim of analyzing, describing and knowing the innovative activities carried out during the Covid-19 pandemic at TBM Teras Baca Sekar Kinasih Sidareja. The approach used is a qualitative approach with data collection carried out by means of observation, interviews and documentation. The primary data source used interviews with the managers of the reading terrace nowadays. Secondary data sources come from documents related to research. The research data were analyzed using the analysis of the interaction model of Milles and Huberman which originated from four activities, namely data collection, data reduction, data presentation and data verification. The results showed that the reading terrace was very busy before the Covid-19 pandemic was very crowded with visitors or visitors who came to the reading terrace to borrow books, study computers, and read books on the reading terrace. Readers and the general public who visit the terrace read now. The books that are borrowed and read are books that suit their wants and needs, such as story books, novels, magazines, and business reference books. Visitors and people who visit read the book because they are interested and need information from the book and to gain insight and knowledge. Visitors and the general public who visit can take advantage of and use the facilities provided by the reading terrace TBM now. The facilities provided are various, Wi-Fi, computers, books, a comfortable reading place, etc. to support their fulfillment of information. However, since the covid-19 pandemic, TBM Teras Baca Sekar Kinasih has issued an innovative Football Pick-up Service. This service makes it easy for readers and the general public to meet their information needs without having to visit for some time because of this pandemic, namely the reading terrace staff will provide book lending services by delivering them to visitors by first contacting what books are needed and will be in between. to visitors by the staff of the Teras Baca Sekar Kinasih. Then, with this innovation, the service becomes effective and continues to run even though there has been a decrease in visits and reading interest of readers and the general public as usual. However, this does not become a barrier in carrying out this reading core innovation and remains a practical and efficient innovation.